KONSEPSI ILMU DALAM PERSPEKTIF ABU AL-HASAN AL-‘AMIRI - Muhammad Muzadi Rizki (POTENSIA: Jurnal Kependidikan Islam, 2020)
It cannot be denied that Islamic philosophical thought was influenced by Greek philosophy. Many Muslim philosophers took the thoughts of Aristotle and were interested in Plotin's thoughts. The development of science from the past until now has also always experienced development, as evidenced by the emergence of figures carrying arguments about different concepts of science, starting from Greek philosophers to Eastern philosophers or commonly called Muslim philosophers, for example, from Muslim philosophers there is Abu al-Hasan al-‘Amiri who constructs the paradigm that science and religion are not contradictory but are related to one another, or in other languages not contradicting each other, in which epistemology is still guided by the Qur'an and Hadith.